2016
DOI: 10.1007/s11517-016-1491-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of EEG signal by flicker-noise spectroscopy: identification of right-/left-hand movement imagination

Abstract: Flicker-noise spectroscopy (FNS) is a general phenomenological approach to analyzing dynamics of complex nonlinear systems by extracting information contained in chaotic signals. The main idea of FNS is to describe an information hidden in correlation links, which are present in the chaotic component of the signal, by a set of parameters. In the paper, FNS is used for the analysis of electroencephalography signal related to the hand movement imagination. The signal has been parametrized in accordance with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 60 publications
0
2
1
1
Order By: Relevance
“…A comparison of the difference between C3 and C4 of the two subjects revealed that Subject A exhibited an obvious difference between C3 and C4. However, the results of this study were not completely consistent with the theory [ 28 , 41 ] and suggested that the brain wave measured by the C4 electrode was lower than that by C3 when imagining the movement of the left hand. Conversely, the brain wave measured by the C3 electrode was lower than that by C4 when imagining the movement of the right hand.…”
Section: Resultscontrasting
confidence: 99%
“…A comparison of the difference between C3 and C4 of the two subjects revealed that Subject A exhibited an obvious difference between C3 and C4. However, the results of this study were not completely consistent with the theory [ 28 , 41 ] and suggested that the brain wave measured by the C4 electrode was lower than that by C3 when imagining the movement of the left hand. Conversely, the brain wave measured by the C3 electrode was lower than that by C4 when imagining the movement of the right hand.…”
Section: Resultscontrasting
confidence: 99%
“…In summary, the available evidence collectively suggests that, for both motor skill performance and learning, both PP and CP approach tend to yield superior results compared to MP practiced alone.It has been suggested that MP and PP share similar neural mechanisms in the cognitive process, as evidenced by comparable brain activity during their execution (Jackson et al, 2003;Lee et al, 2019;Matsuo et al, 2020;Nakano, 2012). Specifically, MP has been shown to elicit brain activity in areas such as the primary motor area, premotor area, supplementary motor area, frontal area, parietal area, thalamus, and cerebellum, mirroring the patterns seen during PP (Broniec, 2016;Jackson et al, 2003;Lee et al, 2019;Wang et al, 2014;Zich et al, 2017). Nonetheless, some variations in brain activation have been noted in prior research, where different brain regions are engaged during MP (Di Nota et al, 2016;Macuga & Frey, 2012).…”
Section: Discussionmentioning
confidence: 89%
“…In this study, we replaced the probability in the time domain by the energy spectrum density in the frequency domain to obtain the expression of the energy spectrum in the frequency domain as follows [ 17 , 21 ]: …”
Section: Methodsmentioning
confidence: 99%